NAT10 Maintains OGA mRNA Stability Through ac4C Modification in Regulating Oocyte Maturation - Lin, Jiayu; Xiang, Yuting; Huang, Jiana; Zeng, Haitao; Zeng, Yanyan; Liu, Jiawen; Wu, Taibao; Liang, Qiqi; Liang, Xiaoyan; Li, Jingjie; Zhou, Chuanchuan (Frontiers in Endocrinology, 2022)
In vitro maturation (IVM) refers to the process of developing immature oocytes into the mature in vitro under the micro-environment analogous to follicle fluid. It is an important technique for patients with polycystic ovary syndrome, and especially, those young patients with the need of fertility preservation. However, as the mechanisms of oocyte maturation have not been fully understood yet, the cultivation efficiency of IVM is not satisfactory. We have confirmed in our previous study that oocyte maturation was impaired after N-acetyltransferase 10 (NAT10) knockdown (KD). In this study, we further explored the transcriptome alteration of NAT10-depleted oocytes and found O-GlcNAcase(OGA) was an important target gene for NAT10-mediated ac4C modification in oocyte maturation. NAT10 might regulate OGA stability and expression by suppressing its degradation. To find out whether the influence of NAT10-mediated ac4C on oocyte maturation was mediated by OGA, we further explored the role of OGA in IVM. After knocking down OGA of oocytes, oocyte maturation was inhibited. And as oocytes matured, OGA expression increased and conversely, O-linked N-acetylglucosamine(O-GlcNAc) level decreased. Based on NAT10 KD transcriptome and OGA KD transcriptome data, NAT10-mediated ac4C modification of OGA might play a role through G protein-coupled receptors, molecular transduction, nucleosome DNA binding and other mechanisms in oocyte maturation. And Rsph6a, Gm7788, Gm41780, Trpc7, Gm29036 and Gm47144 were potential downstream genes. Overall, our research focused on the critical gene and mechanisms of NAT10-mediated ac4C modification in oocyte maturation. As our results indicated, NAT10 affected stability of OGA transcript by ac4C modification on it, thus regulated IVM. And our study has revealed the regulation mechanisms of oocytes maturation and provided reference for improving IVM outcomes. At the same time, the interaction between mRNA ac4C modification and protein O-GlcNAc modification was found for the first time, which enriched the regulation network of oocyte maturation.